Needs Analysis for the Development of Snowball Throwing Based Multimedia on Science Learning for Middle School - Putri, Elvy Kartika; Islami, Nur; Hermita, Neni (FKIP-Universitas Riau, 2023)
This research is motivated by students’ struggles in understanding some abstract science concepts and their lack of active involvement in the learning process to develop their thinking skills. Abstract science concepts and student involvement can be achieved through interesting multimedia communication tools. This research is survey research that serves as an initial step in the development of snowball throwing based multimedia. the purpose of this study is to determine what students currently need in science learning and how much students need for the development of snowball throwing based multimedia. the research subjects were junior high school students with a total sample of 72 students and 27 science MGMP (Teacher Forum) teachers selected based on region. The study’s analysis consisted of four indicators: analysis of learning problems, analysis of learning objectives, analysis of students, and analysis of learning settings. According to the study’s result, the information obtained was that the development of snowball throwing based multimedia needed to be developed as a science learning media.